Field sensing in MgO double barrier magnetic tunnel junctions with a superparamagnetic Co50Fe50 free layer - COEY, JOHN (My University, 2012)
Linear response and low frequency noise have been investigated in MgO double barrier magnetic tunnel junctions with a superparamagnetic Co50Fe50 free layer. Linear and hysteresis-free switching was observed for the Co50Fe50 thickness t ≤ 1 nm. A tunneling magnetoresistance ratio of up to 108% and large magnetic field sensitivity value of 61%/mT were obtained at room temperature when t = 1 nm. The angular dependence of magnetoresistance suggests that weak coupling between superparamagneticislands in a t ≤ 1 nm free layer permits continuous rotation of magnetization, whereas the islands in a 0.8nm layer switch rather independently. The frequency dependence of noise power spectrum density and field dependence of Hooge parameter(a) also behave differently for junctions with 0.8 and 1.0nm free layers. The noise sensitivity of 1.0nm free layer junctions is independent of bias, and it is estimated to reach 400 pT/Hz0.5 at 500?kHz
PUBLISHED
Keywords: Physics